Indonesian-English Code-Switching Found In Manggarai Conversations - Patrisius Baur; Ni Nyoman Deni Ariyaningsih; I Made Iwan Indrawan Jendra (ID Solutions, 2021)
This study applied the theory of contact language proposed by Romaine (1988) which distinguish three types of code-switching, namely tag switching, inter-sentential switching, and intra-sentential-switching in order to identify the utterances collected from the conversations of Manggarai people in Nusa Dua Bali. The data were collected through listening and recording, transcribed, analysed, before being discussed descriptively. The study found that all types of theorized code-switching were found with a different distribution. Keywords— Code, Code-Switching, Conversation